A Scoping Review on the Use of Artificial Neural Networks (ANNs) in Decision Adoption Systems (DAS) for Psychological Data Interpretation - Rad, Dana; Paraschiv, Nicolae; Kiss, Csaba (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In the past decade, there has been a surge of interest in the potential of artificial neural networks (ANNs) to enhance decision-making processes in a variety of domains, including decision adoption systems (DAS). This scoping review focuses on the utilization of ANNs in DAS for the interpretation of psychological data. The major goal of this scoping review is to determine the current status of research on the usage of ANNs in DAS for psychological data interpretation and highlight the advantages and limitations of using ANNs in this context. Through a comprehensive search of relevant databases, a range of studies were identified that have employed ANNs in DAS for psychological data interpretation. These studies demonstrate the potential of ANNs to improve decision-making processes in psychological data interpretation, resulting in more accurate diagnoses.. The scoping review presents information on the actual status of research on the usage of ANNs in DAS for psychological data interpretation, offering a comprehensive understanding of the potential of ANNs in enhancing decision-making processes in this context. As such, the findings of this review have significant implications for future research on ANNs in DAS for psychological data interpretation, which may result in the development of more effective decision-making tools for this purpose.